Why should pediatric rheumatology be recognized as a separate subspecialty: an open letter to medical councils and government agencies - Spencer Charles H (BMC, 2007)
Abstract Some pediatric rheumatologists in the West may take for granted that pediatric rheumatology (PR) is a recognized subspecialty. Yet pediatric rheumatology has been accepted as a subspecialty in the United States only since 1990. There are still countries where many pediatric subspecialties are not given official recognition and support, including PR. This lack of recognition delays and impedes the development of PR, appropriate musculoskeletal and rheumatic teaching in medical schools, and optimal diagnosis and treatment for children with these illnesses. In the opinion of editorial staff, each country where pediatric rheumatology is reasonably well developed as a subspecialty has an obligation to help our pediatric rheumatologists elsewhere gain recognition, support, and respect. The Pediatric Rheumatology European Society (PReS) and the Pediatric Rheumatology International Trial Organization (PRINTO) have been leaders in this effort, but in many countries, pediatric rheumatology is still not recognized. This editorial offers rationales and justifications for medical and governmental entities accrediting pediatric rheumatology as a separate subspecialty that may aid in these efforts.